Situating the Jungle-village in Leonard Woolf’s The Village in the Jungle (1913) - Vihanga Perera (Anglica. An International Journal of English Studies)
This paper addresses a gap in literary research in the scholarship on Leonard Woolf’s The Village in the Jungle: a lack of demonstrated understanding on the part of major critics as to what constitutes a village-jungle in the early-20th-century Ceylonese context and, as a result, misunderstanding of the novel’s main characters and events. By drawing on comparative and indigenous sources by writers like R.L. Spittel and Mayaranjan, the paper calls attention to narratives on forest-life as representing a sensibility that is experientially derived; this – in contrast to the claims of Woolf’s critics – brings on a sensibility that lies beyond simplistic claims to “orientalism” and endorsement of colonial views. The discussion centrally draws on the significance of comparative local sources in framing insights to forest life in Ceylon, as the absence of such comparisons hinders the understanding of a novel like The Village in the Jungle to the point of producing readings that prove incomplete and even misleading.